MORPHOFUNCTIONAL CHARACTERISTICS OF THE STRUCTURAL COMPONENTS OF THE PANCREAS EXOCRINE PART IN CHEMICAL CASTRATION - Boruta, N.V.; Shepitko, V.I.; Stetsuk, Y.V.; Dubinin, D.S.; Levchenko, O.A.; Sydorenko, A.V.; Mykhaylenko, V.V. (World of Medicine and Biology, 2023)
Throughout a person’s life, the pancreas, which is the second largest gland (after the liver), is significantly affected by various adverse factors. It is a unique organ that combines external and internal secretory activity, playing an important role in the carbohydrate metabolism of the human body. Today, diseases of the pancreas are one of the most important problems in medicine. Established dystrophic changes of the gland, which were expressed by the formation of fibrous fields, the thickness of the capsule and interlobular connective tissue between the lobes visually increased, a decrease in the area of acini and exocrinocytes was observed, acini lost clear contours and shape due to swelling of the connective tissue. Exocrinocytes of acini lost apical eosinophilia and basal basophilia of the cytoplasm, there was a decrease in the area of the nuclei, which were changed in shape and location. The introduction of triptorelin causes destructive-degenerative changes in the exocrine apparatus of the pancreas, which are characterized by compensatory mechanisms in the early periods of observation, and in the later periods – dystrophic changes in the structural components of the gland are determined, which corresponds to the stage of partial decompensation, a decrease in the activity and functionality of the cellular component of the exocrine apparatus of the pancreas.